Acute bone infarction: a rare complication in thalassemia - Kanthawang T. (2017)
© 2016, ISS. Acute bone infarction is a well-described complication in sickle cell hemoglobinopathy but it is rarely reported in patients with thalassemia. This report describes an 18-year-old man with homozygous β-thalassemia presenting with a fever and severe acute bilateral ankle pain. The acute onset of severe pain and fever were clinical mimics of infectious arthritis and osteomyelitis. Magnetic resonance imaging revealed acute bone infarction in the meta-diaphysis of bilateral tibias presenting as central unenhanced devitalized bone with T1-high signal intensity fluid in the subperiosteum and soft tissue. Characteristic imaging features are discussed, emphasizing the benefit of fat suppression pre-and post-intravenous gadolinium T1-weighted images. The etiologies of bone infarction in thalassemia are reviewed.